A study on the successful factors of an agent in Prudential Assurance Berhad in Melaka / Wan Nazatul Ain Wan Jehari - Wan Jehari, Wan Nazatul Ain (2009)
This research was conducted for the purposed of finding the “Factors to become the successful Agent in Vision Challenges (VC) group in Prudential Assurance Berhad, Melaka”. The main objective of this research was to determine the level of factors to become the successful agents. Those factors are the listening skills, tenacity, well organized, communication skills, personal planning and time management. The problem that occurs in VC group in Prudential Assurance Malaysia Berhad, Melaka is the increasing numbers of terminated agents in these agencies. This problem occurs because of certain reason. The reason may include that they do not know the factors to become successful agent in Prudential Assurance Berhad in Melaka. The respondent of this study would be the agent in the VC group in Prudential Assurance Berhad, Melaka only. 80 questionnaires had been distributed to those residents. The data collection method that been used in this study is using stratified random sampling by using 100 population which aere agents in VC group as the respondents. Then, 80 samples have been determined and questionnaires have been distributed to them. This research has use primary data to collect the data. All the data that been collected have been analyzed using SPSS, Chi- Square, Cross Tabulation and Symmetric Measures. The conclusion of this study was the outcome from the survey analysis and findings. The finding of this study is the most factors that influence the agent to be the successful agent in Prudential Assurance Berhad, Melaka is Listening Skill.